Unveiling geniposide from Paederia foetida as a potential antihypertensive treatment: an integrated approach involving in vivo and computational methods - Chanchal Koley; Arijit Mondal; Suddhsattya Dey; Ravi Rawat; Anjan Mondal; Naresh Kumar Rangra; Deeparani Urolagin; Padmacharan Behera; Dibya Lochan Mohanty; Ameeduzzafar Zafar; Volkan Eyupoglu (SpringerOpen, 2024)
Abstract Background Hypertension is one of the burning topics in today's world. Natural product can open a new window in the treatment as they are lesser side effect compared to synthetic compounds. Paederia foetida a naturally occurring plant has proven its biological importance in many aspects. In this present study, the ethanolic extract of Paederia foetida has effectively proven its antihypertensive activity against Amphetamine-induced hypertension. Results The study was carried out for 4 weeks with five different groups where the groups receiving Paederia foetida (400 mg/kg) for 4 weeks result in decrease in blood pressure and was found helpful in maintaining the sodium and potassium balance in rat's serum. Amphetamine induces decreasing sodium level that can be countered by Paederia foetida whole plant extract. Geniposide, an active ingredient present in this plant, is having antihypertensive activity, so it was docked against different PDB IDs (3OLL, 3OLS, 5DX3, 5DXE & 6PIT), to find its anti-hypertension effectiveness through computational chemistry. The docking investigations identified that estrogen receptor (PDB ID: 3OLS) exhibited the highest possibility to be the site of action. Docking score of Geniposide with 3OLS was -8.91 which is quit comparable with the internal ligand Estradiol. Conclusion To assess the binding affinity of Geniposide with the estrogen receptor, an additional molecular dynamics simulation was conducted. The result strongly suggests that Geniposide has the potential to function as an activator of estrogen receptor through of β-ligand binding. This key finding reveals that Geniposide may serve as a potential in the treatment of hypertension by modulating the activity of the estrogen receptor.